Breastfeeding and the Benefits of Lactation for Women's Health - Luiz Antonio Del Ciampo; Ieda Regina Lopes Del Ciampo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract The offer of the maternal breast to the baby is an unquestionable right of mothers and their children, and all efforts should bemade to promote, follow and maintain exclusive breastfeeding for up to 6months and supplement it until the child completes 2 years of age. Many publications are available in the literature about the qualities of breast milk, its benefits and health repercussions, stimulating the practice of breastfeeding and supporting campaigns for its implementation. However, although it is widely known that breastfeeding is an important step in the reproductive process of women and its practice offers benefits to both mother and child, most of the available information highlights the benefits of breast milk for children, while mention of the effects of breastfeeding on the health of the mother is usually neglected. Thus, the objective of the present study is to highlight the multiple benefits of breastfeeding for the physical and emotional health of the nursing mother. The authors consulted articles published in the databases PubMed, Virtual Health Library andWeb of Science using the keywords breastfeeding, breast milk, lactation and maternal health.